Potential Use of Hyperbaric Oxygen Therapy in Orthodontic Treatment: A Systematic Review of Animal Studies - Akbar, Yun Mukmin; Maskoen, Ani Melani; Mardiati, Endah; Wandawa, Ganesha; Setiawan, Arlette Suzy (European Journal of Dentistry, 2022)
Understanding the fundamental principles of tooth movement could reduce the duration of treatment and achieve a stable outcome, resulting in patient satisfaction. Hyperbaric oxygen therapy was a modality in which a patient inhaled 100% O2 while subjected to high atmospheric pressure. Hyperbaric oxygen therapy facilitated the supply of oxygen to the human body's organs and tissues and served a variety of applications, including patient care and wound treatment. This review article aimed to describe animal studies of the potential effects of hyperbaric oxygen therapy in orthodontic therapy. It was conducted using a systematic literature review method, including searching PubMed and Google Scholar for publications relevant to the research topics. The search was filtered to include only research on orthodontic treatment and hyperbaric oxygen therapy and was published in any year. Articles that did not specify biological components of orthodontic tooth movement (OTM) were excluded. The Preferred Reporting Items identified the papers for the Systematic Reviews and Meta-Analyses (PRISMA) strategy, which resulted in the selection of 11 publications. Hyperbaric oxygen therapy affected parameters of biomarkers representing the clinical, molecular, and cellular biology of bone formation and resorption in periodontal tissues in responding to orthodontic physical forces, including alkaline phosphatase, collagen synthesis, osteoblast, osteoclast, osteocyte, type I collagen, vascular endothelial growth factor, osteocalcin, fibroblast, matrix metalloproteinase-8, transforming growth factor-β, partial pressure of oxygen, partial pressure of carbon dioxide, trabecular bone density, and tooth mobility. Hyperbaric oxygen therapy induced an inflammatory response to follow OTM events during active orthodontic therapy. Hyperbaric oxygen therapy might play a role in the tissue healing process during passive treatment. Nonetheless, additional research should be conducted to establish the efficacy of hyperbaric oxygen therapy in orthodontics.
Keywords: orthodontic treatment; orthodontic tooth movement; hyperbaric oxygen therapy; HBOT; animal studies